Carbonyl sulfide hydrolysis catalyst and preparation method thereof
Through a new preparation method, a honeycomb-shaped carbonylsulfide hydrolysis catalyst is formed, which solves the problems of short service life of existing catalysts and low low temperature hydrolysis efficiency, and achieves efficient COS hydrolysis and long service life.
Patent Information
- Application Number
- CN202411748704.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-11
AI Technical Summary
The existing carbonylsulfide hydrolysis catalyst has a short service life and is not very hydrolyzed under low temperature conditions, which affects the stability and efficiency of the blast furnace gas desulfurization process.
A new preparation method is adopted, including mixing the raw materials of γ-Al2O3, ceria, activated carbon, pore-making agent, binder and water, then immersing in the nano-α-FeOOH solution and calcining twice, and finally impregnating in the titanate coupling agent solution to form a honeycomb-shaped carbonylsulfur hydrolysis catalyst.
The catalyst has a high carbonylsulfide hydrolysis rate at low temperature and has a long service life. After 240 hours of continuous use, the COS hydrolysis rate and H2S generation rate are still above 99%, which significantly improves the stability and efficiency of the process.
Smart Images

Figure BDA0005164431870000091 
Figure BDA0005164431870000101 
Figure BDA0005164431870000102
Abstract
Description
Technical Field
[0001] The invention relates to a carbonyl sulfide hydrolysis catalyst and also to a preparation method of the carbonyl sulfide hydrolysis catalyst. Background Art
[0002] Carbonyl sulfide (COS) can be converted into H2S in the presence of a catalyst, and the generated H2S gas is then removed by a subsequent desulfurizer. Catalytic conversion methods can generally be divided into oxidation conversion, hydrogenation conversion, and hydrolysis conversion. Compared with oxidation conversion and hydrogenation conversion, the hydrolysis conversion method has the following advantages: most of the water vapor required for the hydrolysis process already exists in the raw gas and does not require additional addition; the reaction does not require a hydrogen source, saving energy consumption; there are few side reactions; the price of the hydrolysis catalyst is relatively low, reducing production costs. Therefore, the current mainstream process in the blast furnace gas fine desulfurization market is the hydrolysis conversion desulfurization method. The catalytic efficiency, working conditions and industrial mass production of the carbonyl sulfide hydrolysis catalyst in the hydrolysis conversion desulfurization technology are the key points of the hydrolysis conversion desulfurization process.
[0003] CN113441124A discloses a carbonyl sulfide hydrolysis catalyst and a preparation method thereof. The carbonyl sulfide hydrolysis catalyst is prepared from raw materials including the following components: (1) mixing raw materials including γ-Al2O3, titanium-containing materials, potassium oxide precursor, polyvinyl alcohol, carboxymethyl cellulose, ammonium bicarbonate and a binder, and forming to obtain a green body; (2) drying the green body by hot air method to obtain a dried green body; (3) calcining the dried green body: heating to 400-500°C at a heating rate of 3-10°C / min, and calcining at a constant temperature for 1-5h; then heating to 500-650°C at a heating rate of 5-13°C / min, and calcining at a constant temperature for 1-5h; cooling to obtain a carbonyl sulfide hydrolysis catalyst. However, the service life of the catalyst needs to be further improved.
[0004] CN115869933A discloses a method for preparing a strip-shaped carbonyl sulfide hydrolysis catalyst. The preparation method is as follows: an aluminum source, a zinc source, a magnesium source, an alkali metal compound and an auxiliary agent are extruded to obtain a catalyst precursor; the catalyst precursor is dried and calcined to obtain a calcined product; the calcined product is washed and dried to obtain a carbonyl sulfide hydrolysis catalyst. The preparation process of this catalyst is relatively simple, but compared with a catalyst with through holes inside, the strip-shaped catalyst has a poor specific surface area and pore structure, a slow hydrolysis rate of carbonyl sulfide, poor airflow efficiency, and a large bed pressure drop. Summary of the invention
[0005] In view of this, one object of the present invention is to provide a method for preparing a carbonyl sulfide hydrolysis catalyst, wherein the carbonyl sulfide hydrolysis catalyst obtained by the preparation method has a high carbonyl sulfide hydrolysis rate at low temperature, a long service life and a lasting effect. Another object of the present invention is to provide a carbonyl sulfide hydrolysis catalyst.
[0006] The above technical objectives are achieved through the following technical solutions.
[0007] In one aspect, the present invention provides a method for preparing a carbonyl sulfide hydrolysis catalyst, comprising the following steps:
[0008] (1) mixing raw materials including 60 to 85 parts by weight of γ-Al2O3, 1 to 10 parts by weight of cerium dioxide, 1 to 7 parts by weight of activated carbon, 1 to 10 parts by weight of a pore-forming agent, 1 to 10 parts by weight of a binder and 1 to 10 parts by weight of water, and molding the mixture to obtain a green body;
[0009] (2) immersing the green body in a nano-α-FeOOH solution having a mass fraction of 1 to 6% for 1 to 8 hours, and then calcining the green body once to obtain a primary calcined product;
[0010] (3) The primary calcined product is immersed in a solution of a titanate coupling agent having a mass fraction of 1 to 6% for 1 to 3 hours, and then subjected to secondary calcination and cooling to obtain a carbonyl sulfide hydrolysis catalyst.
[0011] According to the preparation method of the present invention, preferably, the pore-forming agent is selected from one or more of polystyrene, potassium bicarbonate, sodium bicarbonate, potassium hydroxide, phosphoric acid and zinc chloride.
[0012] According to the preparation method of the present invention, preferably, the pore-forming agent is a mixture of polystyrene, potassium bicarbonate and sodium bicarbonate.
[0013] According to the preparation method of the present invention, preferably, the mass ratio of the polystyrene, potassium bicarbonate and sodium bicarbonate is 1:1-1.5:1-1.5.
[0014] According to the preparation method of the present invention, preferably, the binder is selected from one or more of polyacrylic acid, sodium cellulose, polyvinyl alcohol, polyacrylamide, calcium sulfate and calcium oxide.
[0015] According to the preparation method of the present invention, preferably, in step (1), corresponding weight portions of dry raw materials are mixed for 10 to 60 minutes, and then water is added and wet mixed for 20 to 60 minutes to obtain mud; after the mud is formed, it is aged at 50 to 180°C for 20 to 80 minutes, and then the aged blank is calcined at 300 to 800°C for 2 to 8 hours to obtain a honeycomb blank.
[0016] According to the preparation method of the present invention, preferably, in step (2), the primary calcination temperature is 300-450° C. and the primary calcination time is 1-5 h.
[0017] According to the preparation method of the present invention, preferably, in step (3), the secondary calcination temperature is 280-350° C.; and the secondary calcination time is 1-5 h.
[0018] According to the preparation method of the present invention, preferably, the mass fraction of the nano α-FeOOH solution is 2-5%; the mass fraction of the titanate coupling agent is 1-3%.
[0019] On the other hand, the present invention also provides a carbonyl sulfide hydrolysis catalyst, which is prepared by the above method.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] (1) Under relatively low temperature conditions, COS in blast furnace gas can be converted into easily absorbable H2S under the action of the honeycomb hydrolysis catalyst. The generated H2S is then removed by the subsequent inorganic sulfur absorbent, thereby achieving effective control of the total sulfur content of blast furnace gas.
[0022] (2) The active ingredients in the honeycomb catalyst are evenly distributed and highly active, ensuring a high COS hydrolysis conversion efficiency.
[0023] (3) The catalyst has a long service life and lasting effect. After 240 hours of continuous use, the COS hydrolysis rate and H2S generation rate are still above 99%. DETAILED DESCRIPTION
[0024] The present invention is described in more detail below, but the present invention is not limited thereto.
[0025] <Method for preparing carbonyl sulfide hydrolysis catalyst>
[0026] The preparation method of the carbonyl sulfide hydrolysis catalyst of the present invention comprises the following steps: (1) a molding step; (2) a primary impregnation and calcination step; and (3) a secondary impregnation and calcination step.
[0027] In step (1), raw materials including γ-Al2O3, cerium dioxide, activated carbon, pore-forming agent, binder and water are mixed and molded to obtain a green body. Specifically, dry raw materials of corresponding proportions can be mixed for 10 to 60 minutes, and then water is added for wet mixing for 20 to 60 minutes to obtain a mud material; after the mud material is molded, it is aged at a temperature of 50 to 180° C. for 20 to 80 minutes, and then the aged green body is calcined at a temperature of 300 to 800° C. for 2 to 8 hours to obtain a honeycomb green body.
[0028] The mass of γ-Al2O3 can be 60 to 85 parts by weight, preferably 65 to 80 parts by weight, and more preferably 70 to 75 parts by weight. When γ-Al2O3 is used as a catalyst carrier, it can not only provide a suitable pore structure for the active component, but also enhance the activity of the catalyst and improve the selectivity of the catalyst.
[0029] The content of cerium dioxide can be 1 to 10 parts by weight, preferably 2 to 8 parts by weight, and more preferably 4 to 6 parts by weight. This can improve the low temperature sulfate poisoning resistance of γ-Al2O3 and reduce the deposition of elemental sulfur.
[0030] The amount of activated carbon can be 1 to 7 parts by weight, preferably 1 to 5 parts by weight, and more preferably 2 to 3 parts by weight, which can increase the specific surface area of the catalyst, increase the reaction sites, and improve the reaction rate of the catalyst.
[0031] The pore-forming agent can be selected from one or more of polystyrene, potassium bicarbonate, sodium bicarbonate, potassium hydroxide, phosphoric acid and zinc chloride; preferably one or more of polystyrene, potassium bicarbonate, sodium bicarbonate and potassium hydroxide; more preferably a mixture of polystyrene, potassium bicarbonate and sodium bicarbonate. The mass of the pore-forming agent can be 1 to 10 parts by weight, preferably 5 to 10 parts by weight, and more preferably 7 to 9 parts by weight. This can help the carrier to form a more suitable pore structure, facilitate the rapid diffusion of hydrogen sulfide, and reduce sulfur deposition.
[0032] The binder can be selected from one or more of polyacrylic acid, sodium cellulose, polyvinyl alcohol, polyacrylamide, calcium sulfate and calcium oxide, preferably one or more of polyacrylic acid, sodium cellulose, polyacrylamide, calcium sulfate and calcium oxide, more preferably calcium sulfate or calcium oxide. The mass of the binder can be 1 to 10 parts by weight, preferably 2 to 8 parts by weight, more preferably 3 to 6 parts by weight. This can facilitate the formation of the carrier, the pores, and improve the hydrolysis performance and stability of the catalyst.
[0033] The mass of water may be 1 to 10 parts by weight, preferably 3 to 8 parts by weight, and more preferably 4 to 6 parts by weight.
[0034] In the present invention, the raw material mixing time may be 10 to 60 min, preferably 15 to 40 min, and more preferably 20 to 30 min.
[0035] In the present invention, the wet mixing time may be 20 to 60 min, preferably 20 to 40 min, and more preferably 20 to 30 min.
[0036] In the present invention, the drying and aging temperature of the honeycomb mud segment can be 50-180° C., preferably 90-150° C., and more preferably 100-120° C. The drying and aging time of the honeycomb mud segment can be 20-80 min, preferably 30-70 min; and more preferably 40-60 min.
[0037] In the present invention, the calcination temperature of the honeycomb embryo body can be 300-800° C., preferably 400-700° C., more preferably 500-650° C. The calcination time of the honeycomb embryo body can be 2-8 hours, preferably 3-7 hours, more preferably 5-7 hours.
[0038] In step (2), the green body is immersed in a nano-α-FeOOH solution with a mass fraction of 1 to 6% for 1 to 8 hours, and then calcined once to obtain a green body after calcination.
[0039] Nano-α-FeOOH can be prepared by the following method:
[0040] FeCl3·6H2O is dissolved in an ethanol solution to obtain a first mixed solution; polyvinyl pyrrolidone is dissolved in an ethanol solution to obtain a second mixed solution; the second mixed solution is added to the first mixed solution by a dropper, and then ammonia water and ammonium fluoride solution are added in sequence to obtain a third mixed solution; the third mixed solution is transferred to a stainless steel reactor lined with polytetrafluoroethylene, reacted at 150-200°C for 3-8h, cleaned and dried to obtain nano α-FeOOH.
[0041] The mass fraction of aqueous ammonia may be 20 to 40 wt %, preferably 20 to 35 wt %, and more preferably 25 to 30 wt %.
[0042] The reaction temperature may be 150 to 200° C., preferably 170 to 190° C., more preferably 180 to 190° C. The reaction time may be 3 to 8 h, preferably 4 to 7 h, more preferably 5 to 7 h.
[0043] Nano-α-FeOOH is dissolved in deionized water to prepare a nano-α-FeOOH solution. The mass fraction of the nano-α-FeOOH solution can be 1-6%, preferably 2-5%, and more preferably 3-4%. The immersion time can be 1-8 hours, preferably 2-6 hours, and more preferably 3-5 hours. The immersion liquid temperature can be 40-60°C; preferably 45-55°C; and more preferably 50-55°C.
[0044] The drying temperature may be 100 to 250° C., preferably 120 to 220° C., more preferably 150 to 200° C. The drying time may be 1 to 4 hours, preferably 1 to 3 hours, more preferably 2 to 3 hours.
[0045] The primary calcination temperature may be 300 to 450° C., preferably 320 to 400° C., more preferably 350 to 380° C. The primary calcination time may be 1 to 5 hours, preferably 2 to 4 hours, more preferably 2 to 3 hours.
[0046] In step (3), the green body after the primary calcination is immersed in a solution of a titanate coupling agent with a mass fraction of 1 to 6% for 1 to 3 hours, and then subjected to secondary calcination and cooling to obtain a carbonyl sulfide hydrolysis catalyst.
[0047] The mass fraction of the titanate coupling agent solution can be 1-6%, preferably 1-3%, and more preferably 1-2%. The immersion time can be 1-3 hours, preferably 1-2.5 hours, and more preferably 2-2.5 hours. Such a titanate coupling agent loading can increase the basic active centers on the catalyst surface, improve the COS hydrolysis conversion rate, improve the catalyst's anti-oxidation poisoning performance, and extend its service life.
[0048] The drying temperature may be 50 to 100° C., preferably 60 to 90° C., more preferably 70 to 80° C. The drying time may be 1 to 4 hours, preferably 1 to 3 hours, more preferably 2 to 3 hours.
[0049] The temperature of the secondary calcination can be 280-350°C, preferably 300-340°C, and more preferably 300-320°C. The time of the secondary calcination can be 1-5h, preferably 2-4h, and more preferably 2-3h. Such calcination steps and calcination conditions are conducive to the formation of the internal pore structure of the honeycomb carrier, the loading of the active components on the carrier material, the diffusion of blast furnace gas in the honeycomb carbonyl sulfide hydrolysis catalyst and the performance of the hydrolysis catalytic performance, while ensuring the structural stability of the honeycomb carbonyl sulfide hydrolysis catalyst after loading the active components.
[0050] <Carbonyl sulfide hydrolysis catalyst>
[0051] The present invention also provides a carbonyl sulfide hydrolysis catalyst, which is prepared by the method described above. The honeycomb catalyst of the present invention has a rich pore structure and a uniform load of active ingredients, and can efficiently hydrolyze COS. When COS is hydrolyzed to generate H2S, H2S can quickly diffuse from the inside of the catalyst to the main gas phase, thereby reducing the chance of poisoning of the carbonyl sulfide hydrolysis catalyst. At the same time, the carbonyl sulfide hydrolysis catalyst prepared by the present invention has a long service life and a lasting effect. After continuous use for 240 hours, the COS hydrolysis rate and the H2S generation rate are still above 99%.
[0052] Here are some sources of raw materials:
[0053] γ-Al2O3 was purchased from Yangzhou Zhongtianli New Materials Co., Ltd.;
[0054] Titanate coupling agent was purchased from Nanjing Nengde New Material Technology Co., Ltd.
[0055] Preparation Example 1
[0056] FeCl3·6H2O is dissolved in an ethanol solution to obtain a first mixed solution; polyvinyl pyrrolidone is dissolved in an ethanol solution to obtain a second mixed solution; the second mixed solution is added to the first mixed solution by a dropper, and then 25wt% ammonia water and ammonium fluoride solution are added in sequence to obtain a third mixed solution; the third mixed solution is transferred to a stainless steel reactor lined with polytetrafluoroethylene, reacted at 180°C for 6h, washed with deionized water and ethanol, and dried at 60°C to obtain nano α-FeOOH; finally, the nano α-FeOOH is configured into a nano α-FeOOH solution with a mass fraction of 4%.
[0057] Preparation Example 2 and Comparative Preparation Examples 1 to 2
[0058] The dry raw materials shown in Table 1 were mixed for 30 minutes, and then deionized water was added and wet mixed for 30 minutes to obtain a slurry. After the slurry was formed, it was aged at 110° C. for 60 minutes, and then the aged blank was calcined at 600° C. for 6 hours to obtain a honeycomb blank.
[0059] Table 1
[0060] Element Preparation Example 2 Comparative Preparation Example 1 Comparative Preparation Example 2 <![CDATA[γ-Al2O3]]> 75 parts by weight 76 parts by weight 77 parts by weight Cerium Oxide 5 parts by weight 5 parts by weight 3 parts by weight Activated carbon 2 parts by weight 1 part by weight 2 parts by weight Polystyrene 3 parts by weight 3 parts by weight 3 parts by weight Potassium bicarbonate 3 parts by weight 3 parts by weight 3 parts by weight Sodium bicarbonate 3 parts by weight 3 parts by weight 3 parts by weight Calcium sulfate 5 parts by weight 5 parts by weight 5 parts by weight Deionized water 5 parts by weight 5 parts by weight 5 parts by weight
[0061] Example 1
[0062] The honeycomb green body obtained in Preparation Example 2 was immersed in the nano-α-FeOOH solution with a mass fraction of 4% obtained in Preparation Example 1 for 4 hours, and then taken out and allowed to stand to obtain a primary impregnation green body, and then the primary impregnation green body was dried at 200°C for 2 hours to obtain a dried primary impregnation green body. The dried primary impregnation green body was once calcined at 370°C for 3 hours to obtain a primary calcination product; then the primary calcination product was immersed in a titanate coupling agent solution with a mass fraction of 1% for 2 hours, and then taken out and allowed to stand to obtain a secondary impregnation product; then the secondary impregnation product was dried at 80°C for 2 hours, and then secondary calcined at 300°C for 3 hours, and then cooled to obtain a carbonyl sulfide hydrolysis catalyst.
[0063] Comparative Example 1
[0064] The green body of Preparation Example 2 was replaced by the green body obtained in Comparative Preparation Example 1, and the remaining operations and parameters were the same as in Example 1.
[0065] Comparative Example 2
[0066] The green body of Preparation Example 2 was replaced by the green body obtained in Comparative Preparation Example 2, and the remaining operations and parameters were the same as those in Example 1.
[0067] Comparative Example 3
[0068] The honeycomb green body obtained in Preparation Example 2 was immersed in the nano-α-FeOOH solution with a mass fraction of 4% obtained in Preparation Example 1 for 4 hours, taken out and allowed to stand to obtain a primary impregnation green body, and then the primary impregnation green body was dried at 200°C for 2 hours to obtain a dried primary impregnation green body. The dried primary impregnation green body was once calcined at 370°C for 3 hours to obtain a primary calcination product; then the primary calcination product was immersed in a NaOH solution with a mass fraction of 1% for 2 hours, taken out and allowed to stand to obtain a secondary impregnation product; then the secondary impregnation product was dried at 80°C for 2 hours, and then secondary calcined at 300°C for 3 hours, and the carbonyl sulfide hydrolysis catalyst was obtained after cooling.
[0069] Experimental example
[0070] The performance of the carbonyl sulfide hydrolysis catalyst was tested by the following method: the carbonyl sulfide hydrolysis catalyst was filled into a fixed bed reactor, and the carbonyl sulfide concentration of the inlet flue gas was 120 mg / Nm 3 , moisture content 0.1wt%, at a space velocity of 1500h -1 The performance of the carbonyl sulfide hydrolysis catalyst was tested under the conditions of 240 hours of continuous testing and a temperature of 70°C. The results are shown in Table 2.
[0071] (1) The calculation method of carbonyl sulfide hydrolysis rate is as follows:
[0072] The carbonyl sulfide (COS) hydrolysis rate refers to the ratio of COS that undergoes hydrolysis to the amount of imported COS. The calculation formula is as follows:
[0073]
[0074] Where η cos —COS hydrolysis rate, %;
[0075] C m —Average inlet concentration of COS, mg / Nm 3 ;
[0076] C i —COS outlet concentration (i=1,2,3,…), mg / Nm 3 .
[0077] The calculation method of hydrogen sulfide generation rate is as follows:
[0078] The hydrogen sulfide (H2S) generation rate refers to the ratio of the actual H2S generated by hydrolysis to the theoretical amount of H2S generated by complete hydrolysis of COS. The calculation formula is as follows:
[0079]
[0080] Where η H2S —H2S generation rate, %;
[0081] C n —Theoretically, the average concentration of H2S produced by complete hydrolysis of COS, mg / Nm 3 ;
[0082] C j —H2S outlet concentration (i=1,2,3,…), mg / Nm 3 .
[0083] (2) Determination method of porosity and pore volume:
[0084] The pore volume and porosity of the hydrolysis catalyst in the present invention were measured using the American Micromeritics ASAP 2460 fully automatic rapid physical adsorption analyzer based on the working principle of the isothermal physical adsorption static volume method.
[0085] Table 2
[0086]
[0087] As can be seen from Table 2, the porosity and pore volume of the catalyst of the present invention are larger than those of the comparative example, indicating that the pore structure of the catalyst is richer and the active component loading is more uniform. In a low temperature environment of 50 to 100° C., the COS hydrolysis rate and H2S generation rate are still above 99% after 240 hours of continuous testing, which indicates that the carbonyl sulfide hydrolysis catalyst of the present invention not only has a good catalytic effect but also has a long service life.
[0088] The present invention is not limited to the above-mentioned embodiments. Without departing from the essential content of the present invention, any deformation, improvement and substitution that can be conceived by those skilled in the art shall fall within the scope of the present invention.
Claims
1. A method for preparing a carbonyl sulfide hydrolysis catalyst, characterized in that: The steps include: (1) mixing raw materials including 60 to 85 parts by weight of γ-Al2O3, 1 to 10 parts by weight of cerium dioxide, 1 to 7 parts by weight of activated carbon, 1 to 10 parts by weight of a pore-forming agent, 1 to 10 parts by weight of a binder and 1 to 10 parts by weight of water, and molding the mixture to obtain a green body; (2) immersing the green body in a nano-α-FeOOH solution having a mass fraction of 1 to 6% for 1 to 8 hours, and then calcining the green body once to obtain a primary calcined product; (3) The primary calcined product is immersed in a solution of a titanate coupling agent having a mass fraction of 1 to 6% for 1 to 3 hours, and then subjected to secondary calcination and cooling to obtain a carbonyl sulfide hydrolysis catalyst.
2. The preparation method according to claim 1, characterized in that: The pore-forming agent is selected from one or more of polystyrene, potassium bicarbonate, sodium bicarbonate, potassium hydroxide, phosphoric acid and zinc chloride.
3. The preparation method according to claim 2, characterized in that: The pore-forming agent is a mixture of polystyrene, potassium bicarbonate and sodium bicarbonate.
4. The preparation method according to claim 3, characterized in that: The mass ratio of the polystyrene, potassium bicarbonate and sodium bicarbonate is 1:1-1.5:1-1.
5.
5. The preparation method according to claim 1, characterized in that: The binder is selected from one or more of polyacrylic acid, sodium cellulose, polyvinyl alcohol, polyacrylamide, calcium sulfate and calcium oxide.
6. The preparation method according to claim 1, characterized in that: In step (1), dry raw materials of corresponding weight parts are mixed for 10 to 60 minutes, and then water is added and wet mixed for 20 to 60 minutes to obtain mud; after the mud is formed, it is aged at 50 to 180° C. for 20 to 80 minutes, and then the aged blank is calcined at 300 to 800° C. for 2 to 8 hours to obtain a honeycomb blank.
7. The preparation method according to any one of claims 1 to 6, characterized in that: In step (2), the primary calcination temperature is 300-450° C. and the primary calcination time is 1-5 hours.
8. The preparation method according to any one of claims 1 to 6, characterized in that: In step (3), the secondary calcination temperature is 280-350° C. and the secondary calcination time is 1-5 hours.
9. The preparation method according to claim 1, characterized in that: The mass fraction of the nano-α-FeOOH solution is 2-5%; the mass fraction of the titanate coupling agent is 1-3%.
10. A carbonyl sulfide hydrolysis catalyst, characterized in that: The carbonyl sulfide hydrolysis catalyst is prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Carbonyl sulfide hydrolysis catalyst and preparation method thereof
CN113441124A
Carbonyl sulfide hydrolysis catalyst as well as preparation method and application thereof
CN115869933A